2015
DOI: 10.3748/wjg.v21.i15.4680
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2 expression in mixed gastric carcinoma

Abstract: HER2 detection in mixed gastric carcinoma displays high heterogeneity. Relatively quantitative parameters are needed for assessing the level of HER2 amplification and protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…HER2-positive results by FISH were observed in 11% of cases with an IHC score of 0 and 12% of cases with an IHC score of 1þ. 3 Similarly, other studies 29,[74][75][76][77] have shown HER2 positivity by ISH in up to 14% to 24% of tumors with IHC scores of 0 or 1þ. These patients did not significantly benefit from the addition of trastuzumab to the chemotherapy regimen in the ToGA trial.…”
Section: Strong Recommendationmentioning
confidence: 74%
See 3 more Smart Citations
“…HER2-positive results by FISH were observed in 11% of cases with an IHC score of 0 and 12% of cases with an IHC score of 1þ. 3 Similarly, other studies 29,[74][75][76][77] have shown HER2 positivity by ISH in up to 14% to 24% of tumors with IHC scores of 0 or 1þ. These patients did not significantly benefit from the addition of trastuzumab to the chemotherapy regimen in the ToGA trial.…”
Section: Strong Recommendationmentioning
confidence: 74%
“…The concordance between IHC 3þ and ISH positivity was high, with 94% concordance in the ToGA trial and 62% to 100% in the literature, with most reporting concordance of 90% or higher. 3,8,29,[74][75][76][77][78] Since the benefit from the addition of HER2-directed therapy correlates with HER2 protein expression, initial HER2 testing should be performed by IHC. In situ hybridization should be reserved for IHC 2þ cases.…”
Section: Strong Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…A slight greater HER2 positivity incidence has been reported in EA (24%-35%), more frequently in the subgroup of intestinal-type, in comparison to GC (9.5%-21%) [68][69][70]. It is well known that the rate of HER2 overexpression is strictly related to GC histotype, showing higher frequency in the intestinal histotype (81.6%-91%) in comparison to the diffuse or mixed one (4%-7.9%) [71][72][73][74][75][76][77][78][79]. However, it has been reported an heterogenous pattern of HER2 immunoreactivity in intestinal GEA, exhibiting a combination of HER2-positive and HER2-negative regions [80][81][82][83][84].…”
Section: Her2 In Gastro-oesophageal Malignant Lesionsmentioning
confidence: 96%